2014 7th ESA Workshop on Satellite Navigation Technologies and European Workshop on GNSS Signals and Signal Processing (NAVITEC 2014
DOI: 10.1109/navitec.2014.7045145
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the GPS to Galileo time offset and its validation on a mass market receiver

Abstract: The European GNSS, Galileo is currently in its InOrbit Validation (IOV) phase where four satellites are available for computing the user position. Galileo E1 OS and GPS C/A represent a very effective constellation pair in a consumer grade receiver: the signals are conveyed on the same analog path and measurements can be combined in a single position, velocity and time (PVT) solution, provided that the Galileo to GPS Time Offset (GGTO) is available. Algorithms for GGTO estimation are presented in this paper, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…GPS and Galileo adopt different time scales, hence when GPS and Galileo observables are used together, the clock inter-system bias has to be added in the navigation solution [ 7 ]. Thus, assumes the following form: where are the receiver coordinate differences, expressed in the WGS84 frame.…”
Section: Multi-constellation Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…GPS and Galileo adopt different time scales, hence when GPS and Galileo observables are used together, the clock inter-system bias has to be added in the navigation solution [ 7 ]. Thus, assumes the following form: where are the receiver coordinate differences, expressed in the WGS84 frame.…”
Section: Multi-constellation Solutionmentioning
confidence: 99%
“…Moreover, a composite design matrix is used for the GPS/Galileo case. In this case, the presence of an inter-system bias is accounted for [ 7 ].…”
Section: Integrity Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the rapid evolution of GNSS systems and receivers, the widespread use of combined multi-GNSS receivers in mass-market applications is expected. Gioia et al (2014) demonstrated the benefits of the Galileo plus GPS solution with respect to the GPS-only case in terms of accuracy and availability. This multi-constellation approach increases the available measurements, improving the accuracy and continuity of the position-velocity-time (PVT) solution.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, in the multi-constellation case, the offset is partially known, hence different strategies can be adopted to accommodate for such offset, while in the considered case the offset among the nodes is totally unknown. In [8][9][10], the authors proposed a comparison between different strategies to account for the inter-system bias; analogously, in this paper, a comparison between the proposed approach and the classical method (that does not compensate for the INB) is provided. The INB is composed of two terms: the difference between the network time scales and a device-dependent component.…”
Section: Introductionmentioning
confidence: 99%